Recurrence of post-term pregnancy and associated factors among women who delivered at Kilimanjaro Christian Medical Centre in northern Tanzania: A retrospective cohort study. - Modesta Mitao; Winfrida C Mwita; Cecilia Antony; Hamidu Adinan; Benjamin Shayo; Caroline Amour; Innocent B Mboya; Michael Johnson Mahande (PLoS ONE, 2023)
Background Post-term pregnancy is a health problem of clinical importance and; tends to recur in subsequent pregnancies. Maternal age, height, and male fetal sex are risk factors associated with Post-term pregnancy. The study aimed to determine the recurrence risk of post-term pregnancy and associated factors among women delivered at KCMC referral hospital. Methodology This retrospective cohort study used KCMC zonal referral hospital medical birth registry cohort data for 43472 women delivered between 2000 and 2018. Data were analyzed using STATA version 15 software. Log-binomial regression with robust variance estimator determined the factors associated recurrence of post-term pregnancy adjusted for other factors. Results A total of 43472 women were analyzed. The proportion of post-term pregnancy was 11.4%, and the recurrence was 14.8%. The recurrence risk of post-term pregnancy was increased when a woman had a history of previous post-term pregnancy (aRR: 1.75; 95%CI: 1.44, 2.11). Advanced maternal age, i.e., ≥35years (aRR: 0.80; 95%CI: 0.65, 0.99), having secondary and higher education (aRR: 0.8; 95%CI: 0.66, 0.97), and being employed (aRR: 0.68; 95%CI: 0.55, 0.84) decreased the recurrence risk of post-term pregnancy. Women with recurrence of post-term pregnancy had a higher risk of delivering newborns weighed ≥4000gm (aRR: 5.05; 95% CI: 2.80, 9.09). Conclusion Post-term pregnancy is associated with recurrence risk in subsequent pregnancies. A history of previous post-term pregnancy is associated risk factor and these women are at increased risk of delivering newborns weighed ≥4000gm. Clinical counselling of women at risk of post-term pregnancy and timely management is recommended to prevent adverse neonatal and maternal outcomes.